2014
DOI: 10.1007/s11126-014-9320-8
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Thinking Skills and Impulsivity Dimensions in Conduct and Substance Use Disorders: Differences and Relationships in an Adolescents’ Sample

Abstract: Impact of conduct disorder (CD) and substance use disorder (SUD) on constructive thinking skills and impulsivity was explored. 71 offending adolescents were assessed for CD and SUD. Furthermore, the constructive thinking inventory, the immediate and delayed memory tasks and the UPPS impulsive behaviour scale were administered. Results showed that youths with CD, independently from SUD, presented higher personality impulsivity (urgency) and altered constructive thinking skills (categorical thinking and personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…Indeed, the associations between internalizing and externalizing symptoms with substance use are not consistently demonstrated in community adolescent samples (Colder et al, 2013; McCarty et al, 2013). The fact that early decreases in conduct problems did not mediate intervention effects on alcohol misuse in our study is consistent with studies showing that conduct problems are not causally linked to substance use behaviors, but rather that these behaviors are concurrently related as part of a spectrum of externalizing behaviors (Castellanos-Ryan & Conrod, 2011; Urben et al, 2015). The psychopathology reduction (or affect regulation) mechanism of substance use appears to be more established in individual experiencing harmful alcohol use, or problematic internalizing or externalizing symptoms (Edwards et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the associations between internalizing and externalizing symptoms with substance use are not consistently demonstrated in community adolescent samples (Colder et al, 2013; McCarty et al, 2013). The fact that early decreases in conduct problems did not mediate intervention effects on alcohol misuse in our study is consistent with studies showing that conduct problems are not causally linked to substance use behaviors, but rather that these behaviors are concurrently related as part of a spectrum of externalizing behaviors (Castellanos-Ryan & Conrod, 2011; Urben et al, 2015). The psychopathology reduction (or affect regulation) mechanism of substance use appears to be more established in individual experiencing harmful alcohol use, or problematic internalizing or externalizing symptoms (Edwards et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…These internalizing traits are also risk factors for anxiety and depressive disorders, in turn (Woicik, Stewart, Pihl, & Conrod, 2009). Impulsivity is associated with a multitude of disinhibited behaviors, including conduct disorders (Urben, Suter, Pihet, Straccia, & Stephan, 2015) and polysubstance use (Conrod et al, 2000). Lastly, sensation seeking is associated with risk-taking behaviors for thrill-seeking or enhancement purposes, including binge drinking, but no other psychopathology (Castellanos-Ryan, O'Leary- Barrett, Sully, & Conrod, 2013).…”
mentioning
confidence: 99%
“…University students encounter various problems in their daily lives that must be solved, as they represent a factor of pressure. Furthermore, they undergo vital changes in their lives at the psychological, physiological and behavioural levels, resulting in stress that makes them vulnerable to extreme reactions (Urben et al, 2015). The university stage also has characteristics that contribute to the youth falling into the clutches of extremist groups that allow violence and extremism to subjugate society and the state, and the consequent risks, chaos and destruction of society.…”
Section: Introductionmentioning
confidence: 99%
“…According to Holt et al, 2012), young people with lower self-control consumed more internet pornography. Urben et al, (2015) reported that high impulsivity was associated with low critical thinking, relating this in practice to disturbing situations such as bullying, gender-based violence and sexual harassment of women (Sujung, 2021).…”
Section: Introductionmentioning
confidence: 99%